STUDY OF MATRIX EFFECT ON THE ANALYSIS OF Ni AND Pd BY AAS IN THE DESTRUATS OF HIDROCRACKING CATALYSTS USING AQUA REGIA AND H2SO4 - Wega Trisunaryanti; Mudasir Mudasir; Siti Saroh (Indonesian Journal of Chemistry, 2002)
The matrix effect of various metals on the analysis of nickel and palladium in destruate of catalysts of Butonian asphalt-derived asphaltene by atomic absorption spectroscopy have been investigated. Samples were dissolved by wet decomposition method using aqua regia and then followed by concentrated H2SO4. The solution was evaporated to dryness on a sand-bath. Study of matrix effect was carried out by comparing the absorbance of Ni and Pd with and without the adding of various concentration of metals in the samples. The calibration curve and standard addition methods were applied in the analysis of Ni and Pd. Result of the study showed that matrix effect toward absorbance of Ni is mostly caused by Al and Si contents in the concentration range of 200-500 ppm. Al content in the concentration of 500 ppm, and Si content in the concentration range of 100-500 ppm cause the matrix effect in the analysis of Pd. However, the change in absorbance of Ni and Pd is still below tolerable limit of 10%. The content of Ni in Pd-Ni / zeolit-Y, Ni-Pd/ zeolit-Y, Mo-Ni/ g-alumina, and Ni-Mo / g-alumina with calibration curve technique were 7.44 ± 0.021; 7.62 ± 0.052; 7.75 ± 0.054; and 2.69 ± 0.062 respectively and with standard addition technique were 6.82 ± 0.066; 7.23 ± 0.112; 7.39 ± 0.099; and 2.35 ± 0.055 respectively. Pd content in Pd-Ni / zeolit-Y and Ni-Pd/ zeolit-Y with calibration curve technique were 2.74 ± 0.044 and 2.49 ± 0.051 and with standard addition technique were 2.90 ± 0.015 and 2.69 ± 0.042.